A Construction of a Dynamic Assessment Mechanism for Blended English Writing - Wen, Siqi (Scientific Journal of Technology, 2025)
In recent years, a"teaching-evaluation integrated" assessment model has emerged-Dynamic Assessment(DA), which has gradually become a hot topic for scholars at home and abroad. Whereas the effectiveness of dynamic assessment has been investigated in multiple contexts, it has been under-investigated in the context of blended learning mode for writing performance. To address this gap, this study aims to construct a dynamic assessment mechanism for blended English writing. Based on Vygotsky’s socio-cultural theory,the dynamic assessment theory system is integrated into the entire process of English writing teaching. The author hopes that this paper can lay a solid theoretical foundation for the smooth implementation of dynamic assessment research, construct a reasonable dynamic assessment mechanism, and provide a feasible paradigm for the application of dynamic assessment theory in writing teaching.